INFLUENCE OF THE HOUSEHOLD DETERGENTS ON SOME SERUM BIOCHEMICAL PARAMETERS OF FRESHWATER FISH CHANNA PUNCTATUS (BLOCH). - CHOUDHARY, GEETANJALI; B. S. JHA (The Bioscan, 2013)
The fish Channa punctatus exposed for 30 days to sub lethal concentrations of the detergents Nirma (9.50 mg/L) and Tide (37.0 mg/L) registered a significant (p<0.001) increase in serum glucose by 50.72% and 39% respectively whereas serum protein decreased by 43.47% (p<0.01) and 25.87% (p<0.05) under Nirma and Tide exposure respectively. The serum cholesterol elevated by 52.47% (p<0.001) in Nirma and 26.15% (p<0.01) in Tide exposed fish groups. The enzymatic activities of serum glutamate oxaloacetate and glutamate pyruvate transaminases and alkaline phosphatases also increased significantly (p<0.001) under the toxic influence of both the detergents. Contrary to this, the activity of acid phosphatases was found to be significantly (p<0.01) inhibited by 45.2% and 33.12% as a consequence of Nirma and Tide exposure respectively. The magnitude of alterations in the serum biochemical parameters were evidently greater under the influence of Nirma thereby indicating higher sensitivity of the fish to this detergent. This study concludes that both the detergents, even at safe doses, are quite potent to manifest physio-metabolic crisis in the fish and that each of the above biochemical indices may be used as bioindicator of detergent toxicity in fish.